Fundamentals or financialisation of commodity markets: What determines recent wheat prices? - Bernhard Troester; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2013)
Food price developments have various impacts at the country and household level, in particular in developing countries with severe implications on food security, poverty and economic stability. The focus of this paper is on wheat as it is, together with rice, the most important food crop. The analysis focuses on the determinants of recent wheat price developments, in particular on the role of fundamental supply and demand factors and the financialisation of commodity markets, i.e. the increasing presence of financial investors. The paper gives an overview of the relevance of wheat in the global food production system, recent wheat price developments, and different determinants of wheat prices stated in the literature, in particular the controversial debate on the influence of financial investors. It adds to this debate by employing a basic supply and demand model for global wheat prices based on the main fundamental demand and supply factors stated in the literature. The model can replicate actual wheat prices up to 2006/07 but a significant divergence appears thereafter. This gap may be explained by non-fundamental factors, most importantly financialisation.
Keywords: 330; Weizenpreis; Weizen; Spekulation; Globalisierung; Finanzkapitalismus; Finanzmarktregulierung; Welt